MetaSearching and Beyond: Implementation Experiences and Advice from an Academic Library - Herrera, Gail (Information Technology and Libraries, 2007)
In March 2003 the University of Mississippi Libraries made our MetaSearch tool publicly available. After a year of working with this product and integrating it into the library Web site, a wide variety of libraries interested in our implementation process and experiences began to call. Libraries interested in this product have included consortia, public, and academic libraries in the United States, Mexico, and Europe. This article was written in an effort to share the recommendations and concerns given. Much of the advice is general and could be applied to many of the MetaSearch tools available. Google Scholar and other open Web initiatives that could impact the future of MetaSearching are also discussed.